2019
DOI: 10.1111/mpp.12897
|View full text |Cite
|
Sign up to set email alerts
|

Soybean RNA interference lines silenced for eIF4E show broad potyvirus resistance

Abstract: Soybean mosaic virus (SMV), a potyvirus, is the most prevalent and destructive viral pathogen in soybean‐planting regions of China. Moreover, other potyviruses, including bean common mosaic virus (BCMV) and watermelon mosaic virus (WMV), also threaten soybean farming. The eukaryotic translation initiation factor 4E (eIF4E) plays a critical role in controlling resistance/susceptibility to potyviruses in plants. In the present study, much higher SMV‐induced eIF4E1 expression levels were detected in a susceptible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 61 publications
(136 reference statements)
0
18
0
Order By: Relevance
“…As the high similarity of SceIF4Ea and SceIF4Eb made differences difficult to be distinguished by RT-qPCR, their expression profiles were combined using one pair of primers. The results showed that the expression levels of SceIF4Ea/b , SceIF(iso)4E, and ScnCBP were upregulated upon infection and then downregulated to the level of the control or slightly higher than the control level ( Figure 3 ), which is similar to the soybean response to the Soybean mosaic virus infection [ 54 ].…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…As the high similarity of SceIF4Ea and SceIF4Eb made differences difficult to be distinguished by RT-qPCR, their expression profiles were combined using one pair of primers. The results showed that the expression levels of SceIF4Ea/b , SceIF(iso)4E, and ScnCBP were upregulated upon infection and then downregulated to the level of the control or slightly higher than the control level ( Figure 3 ), which is similar to the soybean response to the Soybean mosaic virus infection [ 54 ].…”
Section: Resultsmentioning
confidence: 72%
“…Furthermore, most of the mutant lines show no growth defects. A study of these mutants led to the discovery of the molecular nature of plant recessive resistance to plant viruses [ 42 , 52 , 53 , 54 ]. To date, 14 natural recessive resistance genes corresponding to eIF4E or its isoform eIF(iso)4E against plant viruses have been identified from diverse plant species [ 37 , 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…These transgenic lines were generated either by overexpressing resistance genes or by introducing SMV genetic elements to induce pathogen-derived resistance (PDR) [133]. A recent study documented a transgenic soybean that targets the soybean endogenous gene, eIF4E, via an RNA interference approach [134]. The eIF4E protein is required for the accumulation of the several potyviruses, and thus is considered as a major susceptibility factor for several RNA viruses [135].…”
Section: Stimulates Aba Accumulation [25]mentioning
confidence: 99%
“…Attenuated SMV-Coat-protein mediated-resistance transgenic soybean Highly resistant to SMV strain D and A (in Japan) [138] SMV-CP-RNAi transgenic soybean Induces a functional gene silencing system and resulted in a viral-resistant phenotype. [139] Inverted repeat-SMV-HC-pro transgenic soybean Induced RNA-mediated resistance via RNAi by targeting SMV-HC-pro [140] Soybean RNA interfere lines, silenced for eIF4E Interferes viral replication cycles, increases broad-spectrum resistance against SMV-SC3, SC7,SC-15,SC18, and SMV-R [134]…”
Section: Tolerance Cultivar Referencementioning
confidence: 99%
“…SMV, a member of the genus Potyvirus in the family Potyviridae , has a single-strand RNA genome that encodes a single large open reading frame (ORF) ( Hajimorad et al, 2018 ; Gao et al, 2019 ). The translated polyprotein yields a series of multifunctional proteins through proteolysis, which are commonly named P1, HC-Pro, P3, PIPO (a product of slippage in the P3 coding sequence), 6K1, CI, 6K2, VPg, NIa-Pro, NIb, and CP ( Hajimorad et al, 2018 ; Gao et al, 2019 ). SMV is naturally transmitted by aphids in a nonpersistent manner but can also be transmitted through infected seeds ( Widyasari et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%